Bellevalia koyuncui sp. nova (Asparagaceae): a new species from South Eastern Anatolia, Turkey - Karabacak, Osman; Yildirim, Hasan; Marti̇n Esra (Phytotaxa, 2015)
Bellevalia Lapeyrouse (1808: 425) is a genus comprising about 65 species and subspecies distributed over the Mediterranean region (Bareka et al. 2008, Jafari & Maassoumi 2008, Borzatti von Loewenstern et al. 2013). Wendelbo (1984) reported 18 taxa, seven of which endemic to the country. In further studies, Wendelbo (1985) reduced Bellevalia latifolia Feinbrun (1940: 369) to a synonym of B. olivieri (Baker 1874: 8) Wendelbo (1985: 120). Since then, three species were published by Özhatay (2000), while Johnson (2003) reduced B. pycnantha (Koch 1849: 255) Losinskaja (1935: 310) to a synonym of B. paradoxa (Fischer & Meyer 1835: 30) Boissier (1882: 308). In recent years, four more species, B. leucantha Persson (2006: 253), B. malatyaensis Uzunh. & H.Duman in Uzunhisarcıklı et al. (2013: 652), B. chrisii Yıldırım & B.Şahin in Yıldırım et al. (2015: in press) and B. pseudolongipes Karabacak & Yıldırım in Karabacak et al. (2014: 210) were described. In this study, we present a further new species, Bellevalia koyuncui, endemic to Turkey.